ECOLOGICAL ANALYSIS OF ANTHROPOGENIC IMPACT ON THE QUALITY OF VACCINIUM OXYCOCCOS L. FRUITS IN YAVORIV DISTRICT - Snitynskyi В.; Lysak Г.; Khirivskyi П.; Liubynets Н.; Panas Н.; Kalyta Р. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Recent studies examining the dynamics of successional changes in plant swamp communities within the Roztochchia area have been analyzed. Most findings indicate concerning trends regarding the drying of swamps in the region. This environmental challenge leads to irreversible alterations in natural landscapes. Swamps, as a biome, play a crucial role in the ecosystem by purifying water sources, stabilizing microclimate variations, mitigating flood risks, enhancing water quality, and preserving the biodiversity of swamp territories. Eight localities of Vaccinium oxycoccos habitats in Yavoriv area have been described. Given their low productivity, these areas are not suitable for large-scale harvesting. However, it is noteworthy that their ecological and phytocenotic conditions are satisfactory for the current period. Particular attention is paid to the “Nemyriv” trial area, which exhibits positive hydrological dynamics and maintains its status as a wetland. Consequently, the population of bog cranberry in this region is on the rise and remains largely unaffected by human activities. The dense swamp thickets of trees and shrubs prevent visitors to the sanatorium from moving freely around this area. The habitats of V. oxycoccos in nature conservation areas are in a poorer state. There are negative effects stemming from human influence on the cranberry groves within the Novoyavorivsk forestry. This has led to trampling of paths, formation of deep passages between Sphagnum moss cushions, and alterations in hydrological conditions and swamp vegetation cover. The chemical composition of bog cranberry was analyzed on experimental plots of Nemyriv, Novoyavorivsk, Shavari, Rohizno, as well as the Yavoriv military training ground and Yavorivskyi National Nature Park. The causes of anthropogenic pressure on the cranberry population were examined, and an excess of the maximum permissible concentrations (MPC) of Cd, Fe, and Cr in V. oxycoccos berries was detected across all test areas. The transboundary location of the territory and the geological and historical characteristics of the region were recognized as the main reasons for the contamination of the berries. The factors influencing plant populations were studied, and measures were proposed to normalize the MPC levels of the aforementioned elements in the studied ecotopes.